1998
DOI: 10.1097/00004714-199808000-00002
|View full text |Cite
|
Sign up to set email alerts
|

A Canadian Multicenter Study of Three Fixed Doses of Controlled-Release Ipsapirone in Outpatients With Moderate to Severe Major Depression

Abstract: Ipsapirone, an azapirone with 5-hydroxytryptamine (5-HT1A) partial agonist activity, has been shown in preliminary studies to be effective in the treatment of major depressive disorder. This 8-week, randomized, double-blind study compared the efficacy, safety, and tolerability of three fixed doses of controlled-release ipsapirone (10-, 30-, and 50-mg dose once daily) with placebo in 410 patients with moderate to severe major depression (Hamilton Rating Scale for Depression [HAM-D] score > or = 20). The 10-mg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Furthermore, no positive double-blind placebo-controlled reports of antidepressant activity in depressed patients have been reported for the 5-HT 1A partial agonists tandospirone and flesinoxan. A large multicenter, double-blind, placebo-controlled trial for ipsapirone failed to observe a significant antidepressant response, despite a placebo response rate of only 35% (Lapierre et al, 1998). Finally, it should be noted that no 5-HT 1A partial agonists have been approved by the FDA for the treatment of major depression.…”
Section: Therapeutic Efficacy Of Ssris: Which 5-ht Receptors Are Actimentioning
confidence: 98%
“…Furthermore, no positive double-blind placebo-controlled reports of antidepressant activity in depressed patients have been reported for the 5-HT 1A partial agonists tandospirone and flesinoxan. A large multicenter, double-blind, placebo-controlled trial for ipsapirone failed to observe a significant antidepressant response, despite a placebo response rate of only 35% (Lapierre et al, 1998). Finally, it should be noted that no 5-HT 1A partial agonists have been approved by the FDA for the treatment of major depression.…”
Section: Therapeutic Efficacy Of Ssris: Which 5-ht Receptors Are Actimentioning
confidence: 98%
“…Furthermore, drugs that decrease the discharge rate of NRM neurons such as ipsapirone [Fornal et al, 1994], MCPP [Sprouse and Aghajanian, 1988] and 5-methoxydimethyltryptamine [Fornal et al, 1985] precipitate migraine-like headaches with a high degree of reliability [Fozard and Gray, 1989;Lapierre et al, 1998;Yu et al, 1991]. Conversely, drugs like methiothepin, methysergide, and cyproheptadine, which increase the discharge rate of raphe neurons [Blier et al, 1993] have been used to prevent migraine.…”
Section: Nrm and Serotoninmentioning
confidence: 99%
“…Other newer 5HT1A agonists are also being developed; ipsapirone (Stahl et al, 1998) and zalospirone (Rickels et al, 1996) are reported to have greater effectiveness than placebo in controlled trials, while a second trial of iprapirone showed greater efficacy over placebo only for core depressive symptoms (Lapierre et al, 1998). For the serotonin 5HT1A partial agonist flesinoxan, only a small open trial in patients with treatment-resistant depression has been reported (Grof et al, 1993).…”
Section: Serotonin Receptor Antagonists/agonistsmentioning
confidence: 99%